A teoria das inteligências múltiplas e sua relação com o processo de ensino e aprendizado do desenho: um estudo com adolescentes - Fernandes, Márcia Moreno (2005)
This reasearch, along the lines on Education end Arts, had as its main goal to analyze and to verify the development of the Multiple Intelligences of Howard Gardner through the Observational Drawing. Along these lines, we have chosen three particular Multiple Intelligences (Spatial, Cinestesic-corporal and Personal - intra and interpersonal), among the eight available intelligences. The reason for selecting them is that they are more appropriated in Arts teaching. The research was carried out considering undergraduate students doing the first grade on the Design Faculty in a private university, located in the city of Xanxerê (SC). The qualitative research was used as the main tool of investigation, supported by school etnography, which relied on active observation, field diary and documental analysis. The data were collected using the drawings elaborated by the students after each proposal presented by the researcher, as well as photos and notes taken by the researcher and students during the meetings. The results are consistent with the initial expectations, showing the role-played by the drawing in developing the multiple intelligences and presenting the distinct processes taken into account to amplify the personal intelligences, Cinestesic-corporal and spatial.